Heat Transfer Enhancement in a Tube Heat Exchanger Using Discrete Triangular-Prism Roughness Elements - Dolfred Vijay Fernandes (Engineering Proceedings)
Heat exchangers of high effectiveness are generally sought by the thermal industry for the efficient utilization of heat energy. The present study focuses on the enhancement of the effectiveness of a single-tube heat exchanger by attaching equilateral triangular-prism roughness elements on the peripheral heat transfer surface. The forced convection in a circular tube is analyzed using ANSYS-fluent considering air as the working fluid in the Reynolds number (Re) range of 10,000 to 18,000. The geometric parameters (the cross-section and the roughness element height) are fixed. The effects of longitudinal pitch, angular pitch and the orientation of triangular-prism roughness elements on the heat transfer and the frictional energy loss are studied. The presence of roughness elements on the heat transfer surface is found to increase turbulence and fluid mixing. Up to a 23% increase in heat transfer performance is seen in the Nusselt number values of the roughened tube over the smooth tube. The presence of roughness elements on the tube surface also increases the frictional losses; however, this increase is found to be gradual with the reduction in both longitudinal and angular pitch.